Enterprise Architecture Oriented Requirements Engineering for the Design of a School Friendly Open Data Web Interface - Saddiqa, Mubashrah; Kirikova, Marite; Magnussen, Rikke; Larsen, Birger; Pedersen, Jens (Complex Systems Informatics and Modeling Quarterly, 2019)
Open Data is considered a key to scientific innovations. These freely available datasets can also be used as a foundation to enhance the digital and data literacies among the younger generation of school pupils. This article presents the design and prototype of an Open Data web interface based on the Enterprise Architecture Oriented Requirements Engineering (EAORE) approach for Open Data usage as an educational resource in Danish public schools. We first systematically review the literature on Open Data use in educational fields and selected 14 research articles with a particular focus on the use of Open Data in the educational domain after prescribing an inclusion/exclusion criteria on 101 research articles identified initially. The review indicates that there is a gap between Open Data opportunities within the educational domain and in exploring the use of Open Data as a source to develop twenty-first-century skills, specifically digital and data literacies among younger school pupils. To fill this gap, we propose an EAORE approach that represents how Enterprise Architecture (EA) models can guide the overall Requirements Engineering (RE) process for the use of Open Data in Danish public schools. Based on these EA models, we designed the prototype of an Open Data web interface for schools.